STUDI KELAYAKAN PENGEMBANGAN UMKM SABUN AROMA TERAPI DI KABUPATEN BANYUASIN - Novriadhy, Dian; Fatriyanti, Yosi; Juairiyah, Oktaf (Publikasi Penelitian Terapan dan Kebijakan, 2011)
Coconut products in the District of Banyuasin traded in the form of dried meat coconut, coconut oil and coconut fruit (Dogan). These commodity products have little added value. One of the effort to improve the value-added coconut products are processed into soap aromatherapy. Methods of technology transfer is done by demonstration plots, followed by practice by theparticipants. Feasibility was assessed using the criteria of Net Present Value, Benefit Cost Ratio and sensitivity factors. This activity is done with the empowerment of housewives to the development of Micro, Small and Medium Enterprises (MSMEs) in the Village Soap Aroma Therapy Gutters Hallows. The results showed the technology transfer can be easily absorbed bythe participants. Soap products packaged in various forms of packaging and have been sold on a small scale. The results of financial analysis shows this worthy effort developed by the BEP 440 units, B / C ratio of 2.63 and NPV of Rp. 870 000. Assessment of the sensitivity analysis showed this business remain profitable during the production cost increase does not exceed 33% or adecrease in the selling price does not exceed 16.875% of basic price calculation.